ANALISIS KELAYAKAN INVESTASI PROYEK PENGADAAN ALAT PENGEMBANGAN CHAMBER BALAI UJI DENGAN MENGGUNAKAN NET PRESENT VALUE, INTERNAL RATE RETURN DAN PAYBACK PERIOD DI PT DEF - Margana, Riki Ridwan; Syaefulloh, Syaefulloh (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
PT DEF is one of the electronic equipment calibration checking companies in Depok, West Java. PT DEF carries out various checks in the activity chamber to support the successful entry of electronic equipment into Indonesia. The Anechoic Chamber is a chamber designed to absorb electromagnetic waves or sound so that environmental conditions outside the room will not affect the conditions inside the chamber. The Anechoic Chamber. An anechoic chamber is a chamber designed to minimize the reflection of sound waves. This space is lined with thick sound-absorbing material to prevent sound waves from bouncing off the walls, ceiling and floor. This allows accurate measurement of the acoustic characteristics of an object or sound. Anechoic chambers are used in various applications Acoustic research Anechoic chambers are used to research acoustic phenomena, such as sound wave propagation and diffraction. Investment. The anechoic chamber calculation uses Net Present Value (NVP), Internal rate of return (IRR), and Payback Period (PBP). The feasibility of investing in a project to procure test center chamber development equipment can be determined based on the calculation of Net Present Value, Internal Rate of Return and Payback Period. . Based on the results of the NPV calculation, the results obtained were IDR 1,030,241,369,221. So, this investment project can be accepted. Based on the IRR calculation results, the result was 14.803%, meaning that the company's rate of return was greater than the interest rate that the company had to bear. This shows that in the 10th period the company will be able to provide profit results at the level of 14.803%, which is the cutting level. Therefore, the results of this analysis provide investment decisions that are worth implementing. Based on the calculation of the payback period, the Payback Period is less than the maximum amount (10) that can be accepted by the Payback Period, the project can be accepted and continued. In other words, more or less the return on capital from this investment is 8 months